2012
DOI: 10.1073/pnas.1205918109
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of complex knotting and slipknotting patterns in proteins

Abstract: While analyzing all available protein structures for the presence of knots and slipknots, we detected a strict conservation of complex knotting patterns within and between several protein families despite their large sequence divergence. Because protein folding pathways leading to knotted native protein structures are slower and less efficient than those leading to unknotted proteins with similar size and sequence, the strict conservation of the knotting patterns indicates an important physiological role of kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
242
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 228 publications
(244 citation statements)
references
References 50 publications
1
242
0
1
Order By: Relevance
“…Previous investigations on the folding mechanisms of a few knotted proteins established that these proteins have complex multistep folding pathways with slow kinetics rather than the simple two-state mechanisms that are commonly seen for small, fast-folding, single-domain proteins (6)(7)(8)(9)(10)(11). Despite experimental and computational work over the last 10 years (12)(13)(14)(15)(16)(17), the folding mechanisms of knotted proteins remain poorly understood compared with those described for small model systems that have been studied in great detail (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on the folding mechanisms of a few knotted proteins established that these proteins have complex multistep folding pathways with slow kinetics rather than the simple two-state mechanisms that are commonly seen for small, fast-folding, single-domain proteins (6)(7)(8)(9)(10)(11). Despite experimental and computational work over the last 10 years (12)(13)(14)(15)(16)(17), the folding mechanisms of knotted proteins remain poorly understood compared with those described for small model systems that have been studied in great detail (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to these discussions, Rawdon, Stasiak and I studied the presence of subknots, using the spatial closure method discussed earlier, in ideal and random knots [4], the knotting fingerprint, in a generalization of the earlier protein structural analysis [2,6] in which we used another version of a knotting fingerprint. Here, each cell in the circular fingerprint expresses the strength of the knotting of …”
Section: Ideal Knotsmentioning
confidence: 99%
“…We found that loops of the knotted globule were highly knotted, with the knot complexity rising sharply with s. Loops of the unknotted globule, on the contrary, were weakly knotted, and their complexity increased slowly with length. Their knotting complexity was also very variable, indicating the abundance of slip knots [32] (Fig. S5).…”
mentioning
confidence: 99%